Secondary Metabolites From Halotolerant Plant Growth Promoting Rhizobacteria for Ameliorating Salinity Stress in Plants - Sunita, Kumari; Mishra, Isha; Mishra, Jitendra; Prakash, Jai; Arora, Naveen Kumar (Frontiers in Microbiology, 2020)
Soil salinization has emerged as one of the prime environmental constraints endangering soil quality and agricultural productivity. Anthropogenic activities coupled with rapid pace of climate change are the key drivers of soil salinity resulting in degradation of agricultural lands. Increasing levels of salt not only impair structure of soil and its microbial biomass but also restrict plant growth by causing imbalances and metabolic disorders. Potential of secondary metabolites synthesized by halotolerant plant growth promoting rhizobacteria (HT-PGPR) in management of salinity stress in crops is gaining importance. A wide array of secondary metabolites such as osmoprotectants/compatible solutes, exopolysaccharides (EPS) and volatile organic compounds (VOCs) from HT-PGPR have been reported to play crucial roles in ameliorating salinity stress in them and their symbiotic partners. In addition, HT-PGPR and their metabolites also help in prompt buffering of the salt stress and act as biological engineers enhancing the quality and productivity of saline soils. The review documents prominent secondary metabolites from HT-PGPR and their role in modulating plant genetic and metabolic responses to salinity stress. The review also highlights the mechanisms involved in the production of secondary metabolites by HT-PGPR in saline conditions. Utilizing the HT-PGPR and their secondary metabolites for the development of novel bioinoculants for the management of saline agro-ecosystems can be an important strategy in the future.